Grating-assisted coupling to nanophotonic circuits in microcrystalline diamond thin films - Patrik Rath; Svetlana Khasminskaya; Christoph Nebel; Christoph Wild; Wolfram H.P. Pernice (Beilstein Journal of Nanotechnology, 2013)
Synthetic diamond films can be prepared on a waferscale by using chemical vapour deposition (CVD) on suitable substrates such as silicon or silicon dioxide. While such films find a wealth of applications in thermal management, in X-ray and terahertz window design, and in gyrotron tubes and microwave transmission lines, their use for nanoscale optical components remains largely unexplored. Here we demonstrate that CVD diamond provides a high-quality template for realizing nanophotonic integrated optical circuits. Using efficient grating coupling devices prepared from partially etched diamond thin films, we investigate millimetre-sized optical circuits and achieve single-mode waveguiding at telecoms wavelengths. Our results pave the way towards broadband optical applications for sensing in harsh environments and visible photonic devices.